NEWLY ARRIVED STUDENTS: CHALLENGES AND PERSPECTIVES FOR TEACHERS - Birzniece, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The rapidly changing political situation in the world puts an impact on education. After the invasion of Russia in the territory of Ukraine on the 24th of February 2022, the number of refugees in Latvia increased significantly and newly arrived students from Ukraine started learning in the schools of Latvia. In order to facilitate the successful integration of newcomers, Amendment No 48 was accepted by the Cabinet of Ministers of Latvia, which states that newcomers receive their education in Latvia in the state language of Latvia. Therefore, newly- arrived students started learning in schools of Latvia receiving instructions in Latvian. The aim of this publication is to describe the situation of integrating newly arrived students in schools of Latvia from the perspective of a teacher, focusing on difficulties and challenges for a teacher who has no or relatively little experience (ethnic minority students or children of re-migrants) in working with students who have no or relatively poor Latvian language skills at the same time ensuring an inclusive and meaningful educational process.